The effect of use of tzm racing exhaust on exhaust emissions and noise on Nmax motorcycles - Rido Rudiansyah Mohamad; Rahman Huddan; Saepul Rohman Epul; Rohman Fathur; Mardiyana Dani (BIO Web of Conferences)
The Yamaha Nmax is one of the motorbikes that is often used to experience modification racing exhaust. However Thus, impact modification racing exhaust against exhaust emissions and levels noise can cause motorbikes don’t fulfil applicable rules. Study This use method experiment with variable Bound that is level ex-haust emissions (CO, HC, NOx) and levels noise (dB). Fuel used that is Pertamax RON 92. Test results exhaust standard Yamaha Nmax meets emission and noise limits permitted by regulations government. CO emissions are 2.22642 g/kWh and HC are 0.4585 g/kWh, and noise of 72.72 dBa. In contrast, the Nmax and TZM racing exhausts do not fulfil standard, with CO emissions of 36.9873 g/kWh and noise of 96.98 dBa, far exceeds the permitted limits. Therefore, That’s the exhaust standard more friendly environmental and appropriate regulations, temporary racing exhaust does not fulfil criteria the.